Mendeley untuk Semua: Sosialisasi Penggunaan Mendeley untuk Penulisan Akademik dan Non Akademik - Bayu Indra Pratama; Muhammad Rizki Pratama; Dessanti Putri Sekti Ari (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
This article evaluates the role of the reference management application Mendeley, in facilitating citation and information management in the digital age. Mendeley demystifies this complex citation process, making educating the public about its use essential. As part of this effort, the Faculty of Administrative Sciences at Brawijaya University conducted a Zoom-based training program on August 9, 2021, aimed at enhancing the public's skills in using Mendeley. The program aims to assist the public in utilizing technology to manage and cite information for both academic and non-academic purposes. This article details this program's process, outcomes, and impact and demonstrates how Mendeley can improve public access and capability in information management.